Pengembangan Layanan Informasi Karir Berbantuan Media Film untuk Meningkatkan Pemahaman Karir Siswa - Muskita, Sherly Meilany (Widya Warta, 2014)
Guidance and counseling service is an activity conducted to fulfill the function of guidance and counseling. Whereas, the supporting activities are the ones which help the success of the service already given. Information service is a kind of service that enables students to obtain and understand information of great variety (such as information on learning, association, career, follow-up education). Information service is directed to help students to be capable of making decision promptly, concerning either individual, social, learning, or career affairs based on the information they get. This research aims to determine the effectiveness of career information services using films as media to improve students' understanding on career. The subject of the research was 32 students of SMK PGRI Wonoasri, Madiun Regency, in the academic year 2012/2013. The study made use of Educational Research and Development Method. The analysis showed that the result of paired sample t test was 8.111 with sig = 0.000 <0.05. At the error level 5%, the result was 31 t table with df = 2.04. Because t > t table there is a significant increase. The result of t test indicated that the purpose of the development of film-assisted career information services to improve the understanding on career was already achieved.